Manajemen Kurikulum di Pesantren Tradisional dan Modern di Jawa Barat: Studi Kasus Komparatif - Salsabila Putri Maulina; Lantip Diat Prasojo (Media Manajemen Pendidikan, 2026)
This study is motivated by the suboptimal harmonization of religious education and general education in Islamic boarding schools due to differences in curriculum management patterns between traditional and modern Islamic boarding schools, as well as the limited comparative studies that discuss this issue in depth. This study aims to analyze curriculum management in traditional and modern Islamic boarding schools in West Java in integrating religious education and general education. The study uses a qualitative approach with a case study design in one traditional and one modern Islamic boarding school selected purposively. Data were obtained from seven key informants selected purposively, consisting of four informants in the Y modern Islamic boarding school and three informants in the X traditional Islamic boarding school, through in-depth interviews, participant observation, and documentation studies. Data validity was maintained through triangulation of sources and techniques. Data were analyzed using the interactive analysis model of Miles, Huberman, and Saldaña. The results show that traditional Islamic boarding schools implement curriculum management based on values, exemplary behavior, and personal relationships with a pattern of cultural and flexible integration, while modern Islamic boarding schools implement structured, professional, and integrative curriculum management through a formal institutional system and student competency standards. This research contributes by offering a typology of Islamic boarding school curriculum integration as well as a hybrid curriculum management model that combines the strengths of traditional and modern approaches to support the sustainability of Islamic education.